A critical analysis of whether research activities performed by universities fall within the meaning and scope of the term 'educational services' as intended by section 12(h) of the Value-Added Tax Act No. 89 of 1991. Issue 2 (4th May 2017) - Herron, A.
Abstract : According to section 12(h) of the Value-Added Tax Act No. 89 of 1991, 'educational services' are exempt from the levying of value-added tax as imposed by section 7(1)(a) of the Act. The Value-Added Tax Act No. 89 of 1991 does not, however, contain a definition of the term 'educational services' and therefore uncertainty exists in practice regarding the meaning and ambit of the term 'educational services' and whether research conducted by an institution providing higher education would qualify as an 'educational service' or not. The main objective of this article is to investigate whether research activities performed by universities qualify as educational services. In order to meet this objective, South African and international literature was analysed to determine the meaning and scope of educational services. It was found that different categories of research exist (commercial and non-commercial) and, depending on the nature of the research, the treatment is different for value-added tax purposes.